2021
DOI: 10.1177/0896920521991195
|View full text |Cite
|
Sign up to set email alerts
|

The Artisan Economy and the New Spirit of Capitalism

Abstract: Against the backdrop of deindustrialization and the rise of the service economy, small artisan businesses have been promoted as a liberatory alternative to large-scale enterprise and mass production in the wake of the 2007 global financial crisis. We analyze advice manuals for aspiring artisan entrepreneurs by adapting Boltanski and Chiapello’s (2005) framework and analysis of management textbooks to investigate books for would-be artisan business owners. These texts are “manuals of moral instruction” (58) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Similarly, Koch and Sauerbronn (2019) found that craft beer is a sub-culture of consumption where feelings, emotion, and commitment to the cause, play an important role. In terms of craft breweries, numerous authors have found the sector to exhibit a high level of collaboration with both competitors and the communities and customers they serve (Cunningham and Barclay, 2020; Munro and O’Kane, 2021).…”
Section: Craft Beermentioning
confidence: 99%
“…Similarly, Koch and Sauerbronn (2019) found that craft beer is a sub-culture of consumption where feelings, emotion, and commitment to the cause, play an important role. In terms of craft breweries, numerous authors have found the sector to exhibit a high level of collaboration with both competitors and the communities and customers they serve (Cunningham and Barclay, 2020; Munro and O’Kane, 2021).…”
Section: Craft Beermentioning
confidence: 99%
“…Analogamente, riflettere sui principi che sostengono le pratiche artigianali -il dialogo critico tra attori diversi, la possibilità per 157 quegli attori di difendere il proprio stile di vita e valori in contrapposizione all'ideologia (di mercato) dominante -rende possibile pensare il lavoro come un'attività teorico-pratica e il punto di partenza per lo sviluppo di una concezione storica e dialettica del mondo (Gramsci, 2006), riprendendo così la stessa eredità di Freire (Souza, 2022). Un'economia di tipo artigianale come quella che emerge nell'analizzare il lavoro dei birrai brasiliani, inoltre, appare maggiormente democratica, più rispettosa dell'ambiente e offre significative opportunità di autorealizzazione che permettono l'emancipazione e la non-alienazione degli individui (Munro & O'Kane, 2022).…”
Section: Conclusioniunclassified